Dialects, Historical Evidence of Inter-ethnic Language Relations - Kurbonov, Abdulhamid (International Journal of Psychosocial Rehabilitation, 2020)
The study of language in the East, initiated by Mahmud Kashgari in the XI century through areal typological and areal-linguistic methods, the study of dialects and their peculiarities, which are the starting point of any linguistic theories and concepts, is still an important issue today. The emergence of area linguistics in Western linguistics since the XIX century has opened a wide way for a new assessment of problems and concepts in the field of dialectology, solving them in new ways. Historical-comparative and ethno linguistic study of dialects and dialects, based on their theoretical foundations, has been identified as one of the priorities in the holistic study of the language system. The article discusses the peculiarities of the south-western Namangan dialects, their historical genesis, distribution and area of application. The linguistic features and regularities of the rules in dialect are described in a comparative-historical way.